2015
DOI: 10.1039/c4ee03607g
|View full text |Cite|
|
Sign up to set email alerts
|

N-doped graphene quantum sheets on silicon nanowire photocathodes for hydrogen production

Abstract: Photoelectrochemical hydrogen production from solar energy has been attracting much attention in the field of renewable energy technology. The realization of cost-effective hydrogen production by water splitting requires electrolysis or photoelectrochemical cells decorated with highly efficient co-catalysts. A critical requirement for catalysts in the photoelectrochemical cells is not only the ability to boost the 10 kinetics of a chemical reaction but also to exhibit durability against electrochemical and pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
105
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 140 publications
(108 citation statements)
references
References 47 publications
(100 reference statements)
2
105
0
Order By: Relevance
“…In a similar work by Sim et al 83 it was suggested that, these nitrogen doped graphene quantum sheets act as a catalyst for photocataytic hydrogen evolution on Si nanowire photocathodes. Here the time of plasma exposure being 12 seconds only.…”
Section: Nitrogen Functionalizationmentioning
confidence: 95%
“…In a similar work by Sim et al 83 it was suggested that, these nitrogen doped graphene quantum sheets act as a catalyst for photocataytic hydrogen evolution on Si nanowire photocathodes. Here the time of plasma exposure being 12 seconds only.…”
Section: Nitrogen Functionalizationmentioning
confidence: 95%
“…Subsequent studies were aimed at deeper understanding of the enhancement mechanism and performance optimization of N‐GQSs/Si photocathodes. Nam, Hong, and co‐workers designed an electrode based on a Si nanowire array possessing abundant nanostructures and then decorated the array with N‐GQSs for PEC measurements ( Figure ) . In the photo‐electrocatalytic measurements, the nanostructured Si/N‐GQS hybrids gave higher onset potentials and current densities compared to planar Si/N‐GQS hybrids and pure Si‐nanowire arrays.…”
Section: Photocatalytic Hydrogen Evolutionmentioning
confidence: 99%
“…More importantly, it is noteworthy that carbon materials can be engineered to exhibit specific catalytic capabilities for specific electrocatalytic reactions by varying the doping types, sites, and levels [21][22][23][27][28][29][30][31]. Although some of these have recently been developed as HER electrocatalysts [32][33][34], the employment of carbon-based nanomaterials as high-performance [38], (b) schematic showing the steps of the C-PDA film transfer onto Si wafer, (c) and the scheme of synthesis of N-doped carbon using dopamine as a precursor [50][51][52].…”
Section: Introductionmentioning
confidence: 99%